PENGARUH SALES GROWTH, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN FARMASI 2017-2021 - Diffa Fadhillah (Journal of Student Research, 2023)
This study aims to examine the Effect of Sales Growth, Firm Size and Leverage on Tax Avoidance. The population in this study are farmasi sector companies listed on the Indonesia Stock Exchange in 2017-2021. The sampling technique used was purposive sampling method. This study uses panel data regression analysis using the Eviews 9 program in processing data. The results of this study indicate that the Sales Growth Variable has a positive effect and significant on Tax Avoidance, the Firm Size Variable has a nagtive effect and significant on Tax Avoidance, and the Leverage Variable has a no effect on Tax Avoidance.